Immunohistochemical expression of D2-40, VEGF and PCNA as biological markers of lymphangiogenesis, angiogenesis and proliferation in pleomorphic adenoma of salivary gland origin - Rassol, Hiba J; Al-Soudani, Kadhim (Journal of Baghdad College of Dentistry, 2013)
Background: Pleomorphic adenoma is the most common benign salivary gland tumor and shows a pronounced morphological complexity and diversity; for this The immunoprofiles and clinical course of PA differed according to cellular differentiation. Therefore, it is important to assess potential biomarkers in diagnostic and therapeutic trials. This study evaluates the immunohistochemical expression of D2-40, VEGF and PCNA as markers of lymphangiogenesis, angiogenesis and proliferation of PA and their correlation with clinicpathological parameters and with each other. Materials and Methods: Twenty five formalin – fixed, paraffin – embedded tissue blocks were included in this study. After histopathological reassessment of haematoxylin & eosin stained sections for each block, an immunohistochemical staining was performed using anti D2-40, anti VEGF and anti PCNA monoclonal antibodies.Results: Positive immunohistochemical of D2-40, VEGF and PCNA was found in (100%), (92%) and (88%) of the cases respectively. No statistically significant correlation neither among the markers immunoexpression nor with the clinicopathological finding, except a statistical significant correlation was found between (D2-40andVEGF) expression with the histopathological presentation of the cases. Conclusion: D2-40, VEGF and PCNA immunoexpression showed significant correlation with respect to the histopathological presentation of the cases. While no significant correlation seen regarding the expression of aforementioned markers with each other, suggests that each marker might affect on tumor behavior independently.